PRE-SERVICE ENGLISH TEACHERS' PERCEPTIONS TOWARDS THE EFFECT OF CROSS-CULTURAL PEER MENTORING (A CASE OF INDONESIAN PARTICIPANTS OF SEA TEACHER BATCH 8, PANGASINAN STATE UNIVERSITY, THE PHILIPPINES) - Andi Nurul Annisa Budiman (Journal of Innovation Research and Knowledge, 2023)
This study aimed to determine pre-service English teachers' perceptions about effect of cross-cultural peer mentoring. This study used a mixed method design with quantitative and qualitative analysis conducted at Pangasinan State University, Secondary High school department, The Philippines. The researcher adapted the questionnaire from the Intrinsic Motivation Inventory and Interview as the Instruments of this study. There were 22 Indonesian pre-service English teachers as the subject of this study. There are 45 items in the intrinsic motivation inventory (IMI) scale with seven subscales. In this scale, the researcher measures seven aspects. Interest, perceived competence, effort, pressure, perceived choice, value, and relatedness exist. The data analysis showed that 17 (77.28%) pre-service English teachers were positively classified. Pre-service English teachers' responses to the questionnaire with a mean score of 168 (3.73 range of answer). Pre-service English teachers agree that cross-cultural peer mentoring positively affects their intrinsic motivation.